1993
DOI: 10.1038/ng0393-266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein coding regions by database similarity search

Abstract: Sequence similarity between a translated nucleotide sequence and a known biological protein can provide strong evidence for the presence of a homologous coding region, even between distantly related genes. The computer program BLASTX performed conceptual translation of a nucleotide query sequence followed by a protein database search in one programmatic step. We characterized the sensitivity of BLASTX recognition to the presence of substitution, insertion and deletion errors in the query sequence and to sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
987
0
9

Year Published

1995
1995
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,562 publications
(997 citation statements)
references
References 30 publications
1
987
0
9
Order By: Relevance
“…A TBLASTN search [20] was performed against the Expressed Sequence Tag (EST) database with the use of default parameters with reference to the predicted amino acid sequences of both the entire S. cere isiae Cpt1p-coding region and the Cpt1p CDPalcohol phosphotransferase motif [18]. Several ESTs were identified that possessed similarity to either the Cpt1p CDP-alcohol phosphotransferase motif or to other regions within the Cpt1p protein.…”
Section: Isolation and Expression Of The Full-length Hcept1mentioning
confidence: 99%
“…A TBLASTN search [20] was performed against the Expressed Sequence Tag (EST) database with the use of default parameters with reference to the predicted amino acid sequences of both the entire S. cere isiae Cpt1p-coding region and the Cpt1p CDPalcohol phosphotransferase motif [18]. Several ESTs were identified that possessed similarity to either the Cpt1p CDP-alcohol phosphotransferase motif or to other regions within the Cpt1p protein.…”
Section: Isolation and Expression Of The Full-length Hcept1mentioning
confidence: 99%
“…Nucleotide sequences in both directions of overlapping deletion clones were determined by the procedure of Sanger et al (1977), using 7-deaza dGTP to clarify regions previously obscured by GC compression (Mizusawa et al, 1986). Sequence data were compiled and comparative analyses were made using the GCG program (University of Wisconsin, Madison), the BLASTN, BLASTX, and BESTFIT programs developed by the National Centre for Biotechnology Information (Altschul et al, 1990;Devereux et al, 1984;Gish and States, 1993), and the GENECOMPAR program (Applied Maths Department, Kortrijk, Belgium).…”
Section: Dna Preparationmentioning
confidence: 99%
“…1.0 (Cabot and Beckenbach 1989) and GCG (Genetic Computer Group, Madison, Wis.). Homology searches of the sequence databases were performed with the BLASTN and BLASTX algorithms (Altschul et al 1990;Gish and States 1993) using NCBI (National Center for Biotechnology Information) facilities accessed through the network server.…”
Section: Structure Of Psr and Pmentioning
confidence: 99%